Reimagining slavery from a twenty-first-century perspective - Kalous, Isabel (A Comparative Literary History of Modern Slavery: The Atlantic world and beyond, 2025)
This chapter focuses on two historical novels that were published in 2016 to great acclaim: Colson Whitehead’s The Underground Railroad and Yaa Gyasi’s Homegoing (re)imagine slavery from a twenty-first-century perspective. The chapter analyzes the novels’ literary representation of the Atlantic slave trade and slavery and identifies common tropes, metaphors, and images used to convey the traumatic past. It posits that literary approaches to the subject reveal a contemporary desire to revisit the past to address larger social, ideological, and political contexts and discourses that define the present moment. Moreover, it shows that both novels self-consciously reflect on the politics of remembrance and history writin
Keywords: slavery; African diaspora; (neo-)slave narrative; historical fiction; African American literature; post-racial era